Analisis Gaya Kepemimpinan Manajer dan Supervisor Berdasarkan Persepsi Karyawan PT Coast Rejo Indonesia Divisi Produksi - Rahmawati, Siti; Marcian, Deny (IPB University, 2010)
The good leader was the leader who did not use the style of the same leadership, but was matched with the characters of his subordinate. The style of leadership that was applied by the manager and the supervisor in PT Coats Rejo Indonesia must meet with his requirement. The fulfillment of the requirement for this employee could maintain and maximize the long-term achievement of the employee and the company. The aim of this research was (1) to identify the style of leadership applied by the manager and the supervisor at the Division of Production PT Coats Rejo Indonesia, (2) to analize the achievement of the employee at that division, (3) to analize the relationship between the style of leadership and the achievement of the employee, (4) to give the alternative solutions to the company concerning the application of the leadership style for improvement in the future. The results of this research showed that the style of most dominant leadership was applied by the supervisor, and the manager used the style of consultations leadership and participation. The level of the achievement of the employee was good. The relationship of the manager's leadership with the achievement of the supervisor evidently low (the Style of Delegation Leadership) and also the supervisor's leadership with the achievement of the employee and the staff (the Style of Instruction Leadership and Delegation). This research showed that the manager and the supervisor at Division of Production paid attention to the requirement for the employee in applying the style of his leadership.